2020
DOI: 10.1186/s12935-020-01539-7
|View full text |Cite
|
Sign up to set email alerts
|

HKDC1 promotes the tumorigenesis and glycolysis in lung adenocarcinoma via regulating AMPK/mTOR signaling pathway

Abstract: Background Hexokinase domain component 1 (HKDC1) plays an oncogenic role in certain types of cancer, such as lymphoma, liver cancer, and breast cancer. Previous bioinformatics study revealed that HKDC1 was significantly upregulated in lung adenocarcinoma (LUAD). However, its biological functions and potential mechanism in LUAD have not been studied. Methods We performed bioinformatics analysis, quantitative real-time polymerase chain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…mTOR is an important regulator of cell metabolism. Studies have demonstrated that mTOR-mediated glycolysis plays an important role in the tumor cell proliferation and migration 30 , 31 . Therefore, we suspect that mTOR may be the hinge that links CD36 to glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…mTOR is an important regulator of cell metabolism. Studies have demonstrated that mTOR-mediated glycolysis plays an important role in the tumor cell proliferation and migration 30 , 31 . Therefore, we suspect that mTOR may be the hinge that links CD36 to glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Aberrational expression of HKDC1 is associated with various cancers, including colorectal cancer [ 25 ], liver cancer [ 26 ], and breast cancer [ 27 ]. Additionally, Wang and his colleagues reported that HKDC1 was overexpressed in LUAD tissues, and high expression of HKDC1 promoted proliferation, migration, and invasion in LUAD [ 28 ]. Thus, HKDC1 can serve as a prognostic biomarker for LUAD patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Wang and his colleagues reported that HKDC1 was overexpressed in LUAD tissues, and high expression of HKDC1 promoted proliferation, migration, and invasion in LUAD [ 28 ]. Thus, HKDC1 can serve as a prognostic biomarker for LUAD patients [ 28 ]. The aldehyde dehydrogenase (ALDH) superfamily comprises 19 enzymes that play a vital role in maintaining epithelial homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that HKDC1 has an oncogenic function in specific cancer types by different mechanisms, such as liver cancer [ 19 ], breast cancer [ 20 ], lymphoma [ 27 ], colorectal cancer [ 28 ], and lung cancer [ 29 ]. HKDC1 was proven to be substantially expressed in lung adenocarcinoma (LUAD) tissues and cell lines, and a correlation between HKDC1 positive expression with an aggressive phenotype and a poor prognosis in LUAD patients was found by Wang et al HKDC1 overexpression accelerated glycolysis, proliferation, invasion, migration, EMT, and tumorigenicity, while knockdown of HKDC1 had the opposite functional consequences [ 30 ]. From the study of Chen et al, both clinical tumor tissues and breast cancer cells have high levels of HKDC1 expression.…”
Section: Discussionmentioning
confidence: 99%